117k views
1 vote
Please look at the image provided.

Please look at the image provided.-example-1

1 Answer

4 votes

Answer:


x=3

Explanation:


(6\left(x-2\right))/(2)=(3\left(x+5\right))/(8)\\\mathrm{Apply\:fraction\:cross\:multiply:\:if\:}(a)/(b)=(c)/(d)\mathrm{\:then\:}a\cdot \:d=b\cdot \:c\\6\left(x-2\right)\cdot \:8=2\cdot \:3\left(x+5\right)\\Simplify\\48\left(x-2\right)=6\left(x+5\right)\\\mathrm{Expand\:}48\left(x-2\right):\quad 48x-96\\48\left(x-2\right)\\\mathrm{Apply\:the\:distributive\:law}:\quad \:a\left(b-c\right)=ab-ac\\a=48,\:b=x,\:c=2\\=48x-48\cdot \:2\\\mathrm{Multiply\:the\:numbers:}\:48\cdot \:2=96


=48x-96\\\mathrm{Expand\:}6\left(x+5\right):\quad 6x+30\\6\left(x+5\right)\\\mathrm{Apply\:the\:distributive\:law}:\quad \:a\left(b+c\right)=ab+ac\\a=6,\:b=x,\:c=5\\=6x+6\cdot \:5\\\mathrm{Multiply\:the\:numbers:}\:6\cdot \:5=30\\=6x+30\\48x-96=6x+30\\\mathrm{Add\:}96\mathrm{\:to\:both\:sides}\\48x-96+96=6x+30+96\\Simplify\\48x=6x+126\\\mathrm{Subtract\:}6x\mathrm{\:from\:both\:sides}\\48x-6x=6x+126-6x\\\mathrm{Simplify}\\42x=126\\\mathrm{Divide\:both\:sides\:by\:}42


(42x)/(42)=(126)/(42)\\Simplify\\x=3

User KENdi
by
5.4k points